Does Conquest Pay? : The Exploitation of Occupied Industrial Societies - Liberman, Peter (Book collections on Project MUSE., 2011)
Can foreign invaders successfully exploit industrial economies? Since control over economic resources is a key source of power, the answer affects the likelihood of aggression and how strenuously states should counter it. The resurgence of nationalism has led many policymakers and scholars to doubt that conquest still pays. But, until now, the "cumulativity" of industrial resources has never been subjected to systematic analysis. Does Conquest Pay? demonstrates that expansion can, in fact, provide rewards to aggressor nations. Peter Liberman argues that invaders can exploit industrial societies.